Utilization of Rice Flour and Soy Flour with the Addition of Xanthan Gum for Making Gluten-Free White Bread - Ratna Yulistiani; Peni Ambarwati; Yunita Satya Pratiwi; Muhammad Rosyid Wardianto (The University of Lampung, 2025)
Gluten-free white bread formulated with rice and soy flour offers a safe alternative for individuals with celiac disease. Since gluten is absent, xanthan gum is added to improve gas retention and dough structure. This study aimed to identify the optimal formulation of gluten-free white bread by evaluating the physical, chemical, and sensory characteristics of various combinations of rice flour, soy flour, and xanthan gum, as well as analyzing the bread microstructure using Scanning Electron Microscopy (SEM). A Completely Randomized Design (CRD) with two factors- rice flour to soy flour ratios (90:10, 80:20, 70:30) and xanthan gum levels (1%, 2%, 3%)- was performed with three replications. Results showed that the best formula is rice flour to soy flour ratios of 80:20 combined with 3% xanthan gum. The bread had 39.26% water content, 1.26% ash, 10.96% fat, 8.22% protein, and 40.30% carbohydrates. Physically, it had a textural strength of 19.85 N, volume expansion of 82.64%, and porosity of 24.00%. Sensory scores (1-5 scale) were 4.24 (color), 3.92 (aroma), 3.96 (taste), and 4.68 (texture). SEM revealed that the gluten-free bread had larger and less uniform pores. These findings highlight formulation potential to enhance gluten-free bread quality and sensory acceptance.